Construction of Hydrogels with Highly Salt-Resistant Honeycomb Porous Structures for Solar Desalination and Steam Generation - Yang, Jin (Langmuir : the ACS journal of surfaces and colloids, 2024)
Interfacial solar desalination is a method for desalinating seawater using solar energy, and the long-term use of this technology requires a stable evaporation rate and some ability to prevent salt crystallization. To address these issues, carbonized polydopamine-coated bentonite (CPBT), poly(vinyl alcohol), and cellulose nanofibers were used to construct a three-dimensional oriented hydrogel evaporator with a multilayered honeycomb porous structure for long-term desalination. Carbon nanoparticles transferred between the layers of the bentonite, which increases the spacing of the layers and confers a more effective solar light trapping ability. The evaporation rate was 2.26 kg m-2 h-1 in 20 wt % NaCl solution, and no salt crystals were precipitated from the surface of the evaporator in 12 h of continuous operation. This phenomenon occurs due to the wide distribution of pore sizes and the large size of the pores within the evaporator, which create ample space for salt ions to move freely. Furthermore, after undergoing 300 cycles of compression, its internal pore structure remains intact, and the rate of evaporation remains stable. It ensures the evaporator stability during outdoor cycles. The research work provides an effective method to solve the salt accumulation problem and shows its great potential for application